The Impact of Mobilization Power of the Elderly on Welfare Spending for the Elderly in South Korea - Byungkyu Kim; Deokho Cho (European Regional Science Association (ERSA), 2010)
Population structure in current Korea is characterized as "aging society". Under this aging society, the prompt and large-scale expansion of welfare for the elderly is required to meet the welfare demand. To figure out the factors influencing welfare spending, we test how the mobilization power of the elderly which could be instrument to improve their welfare benefits, and political factors such as political competition for a county headman, female share in a local assembly, and election year influence welfare spending for the elderly with 30 local governments for 2000 to 2007. Economic conditions, financial capacity of local governments, financial structural factor, and welfare demand are used as control variable. We find that GRDP, political competition, share of the elderly in population, welfare spending in the previous year, local tax, economic development spending and female share in local assembly influence welfare spending for the elderly. Unfortunately, mobilization power does not affect welfare spending in spite of their higher electoral participation. These results imply the mobilization power is not represented to political mechanism or decision making system, and economic development is the priority for local governments. Generalized Least Square is applied to analyze the model.
Keywords: 330; Decentralization; Mobilization Power; Welfare for the Elderly; Political Competition; Geographical Information System